A Domestic Case Studies Probability to Overcome Software Failures - Ch. Suresh Kumar; D. Raghu; P. Ratna Kumar (Journal of Telematics and Informatics, 2013)
Computers are the pervasive technology of our time. As computer become critically tied to human life, it also becomes more important that interactions with them are under control. They are no longer a novelty, but are integrated into the fabric of our world, performing both high and low-level tasks. That is, computers may be used to eliminate heavy, redundant work and more. Sophisticated machines have been deployed to perform remote surgery or detect subterranean landmines in repopulated civilian areas. The increasing importance of computers in our lives means that it is essential that the design of computer systems incorporates techniques that can ensure reliability, safety and security. This paper will examine technological mishaps involving the use of computers. This review will include notorious software bugs that have affected finance, communication, transit, defense, health and medicine and others systems or industries. The sequence and etiology of these accidents will be discusses as well as how catastrophes may be avoided in the future through lessons and practices based on research.